Hand hygiene, knowledge and training motivational drives: findings from a survey in a university hospital - Corbo, Maria Incoronata; Wachocka, Malgorzata; Pozzi, Maddalena; Cioce, Marco; Di Donato, Michele; Raponi, Matteo; Pascucci, Domenico; Marziali, Eleonora; Fantoni, Massimo; Murri, Rita; Vincenti, Sara; Nuzzo, Carmen; et al. (Frontiers in Public Health, 2024)
This study assessed healthcare workers’ (HCWs) knowledge and adherence to hand hygiene principles in a large Italian university hospital, focusing on identifying knowledge gaps and evaluating training effectiveness. A specifically designed 17-item questionnaire, based on the World Health Organization (WHO) Hand Hygiene Knowledge Questionnaire, was used to measure theoretical knowledge, the role of training, and the impact of experience. The survey had an 8% participation rate (542 responses from a total of 6,749 HCWs), with higher responses among nurses and doctors. Results showed moderate knowledge of hand hygiene protocols, averaging 74%, but revealed gaps in comprehension, particularly in the correct use of hand rub and post-contact sanitation. Logistic regression analysis identified significant predictors of knowledge and adherence, with professional characteristics such as professional qualifications and length of service influencing outcomes (p < 0.05). The findings confirm the strong correlation between hand hygiene knowledge and compliance in reducing healthcare-associated infections (HAIs). Continuous education and customized interventions, including targeted training and feedback, are essential for targeting weak points and improving adherence. These insights emphasize the importance of ongoing training and monitoring to enhance hand hygiene practices, promote a culture of patient safety, and, as a consequence, reduce the incidence of HAIs.